Pedagogy workshops for promoting prosocial behaviour among students : case study - Bičanić, Dajana (Array, 2020)
Prosocial behaviour refers to intentional behaviour aimed at helping others or having a positive influence on others. A community to which a child belongs plays a great role in developing prosocial behaviour. Therefore, great attention should be about the development of the prosocial behaviour in the classroom, which will fully contribute to the student's empathy development, active listening skills, being able to work collaboratively, being able to resolve conflict constructively and self-esteem development as well as self-confidence development. Pedagogical workshops can contribute to a better understanding of a child’s personality. According to that, their focus is on the actual process whose purpose is to provide each participant with the feeling of equality and belonging. The aim of this paper was to investigate whether pedagogical workshops encourage prosocial behaviour in students. The study was conducted during March 2019 and included methodological triangulation (participatory observation, sociometric test and interview) among students of one class departments in a rural area of Slavonia, Croatia. The results of the qualitative research showed that pedagogical workshops provide the conditions necessary to encourage prosocial behaviour in students. Also, the research showed that pedagogical workshops are related to the strengthening of social relations within the group and that certain activities are related to the student's development of empathy, self-confidence and constructive conflict resolution.